On the use of Asymmetric Windows for Reducing the Time Delay in Real-time Spectral Analysis - Florencio, Dinei (ICASSP, 1991)
The idea of asymmetric windowing as a way of reducing time delay in spectral analysis is explored. Traditional windows are analyzed in relation to time delay. Then, some asymmetric windows are introduced and a comparative analysis with traditional windows is made. It is shown that it is possible to reduce the time delay up to about 25% of the analysis window size. Application on LP speech coding is analyzed, and the experimental results of using an asymmetric window on a Standard LPC vocoder are presented.